From technological to social innovation – the changing role of principal investigators within entrepreneurial ecosystems - Carl Johannes (Journal of Management Development, 2020)
Purpose: By taking a micro-level perspective, this paper aims to examine the influence of the ongoing paradigm shift from technological to social innovation on principal investigators (PIs) and thereby links the two emerging research fields of entrepreneurial ecosystems and social innovation. The purpose of this paper is to build the basis for future empirical analyses. Design/methodology/approach: The paper is a conceptual paper and therefore focuses on theoretical considerations. Taking a quadruple helix approach, PIs are outlined as central actors of entrepreneurial ecosystems and transformative agents of the innovation process. Findings: PIs can proactively shape the innovation process and thus the shift from technological to social innovation, through various channels. They can affect all other actors of the quadruple helix, e.g. by exerting influence on the process of scientific change, on the public opinion and/or on the industry partners. Further, the paradigm shift might change the universities' role in the quadruple helix, substantiating their importance in the process of social change. Practical implications: As PIs are influencing all other actors of the quadruple helix, they are central actors of entrepreneurial ecosystems and thus crucial players in the innovation process. Hence, they need to be supported in fulfilling their role of transformative agents, accelerating and shaping the paradigm shift from technological to social innovation. Universities should therefore reconsider their missions and vision as well as their role within the society. Originality/value: This paper considers the influence of an ongoing paradigm shift from technological to social innovation on entrepreneurial ecosystems. This work focuses especially on the PIs' role as transformative agents. Therefore, it builds a bridge from entrepreneurial ecosystems to social innovation and thus contributes to both research fields. Moreover, the paper shows the great potential of PIs to influence and shape social innovation.
Keywords: Entrepreneurial; Innovation sociale; Quadruple helix approach; Réservé UdeM; Technologie; Université